ChemInform Abstract: Cyclic Sulfoxides Garlicnins B2, B3, B4, C2, and C3 from Allium sativum. Issue 2 (14th January 2014) - Nohara, Toshihiro; Fujiwara, Yukio; Ikeda, Tsuyoshi; Murakami, Kohtaro; Ono, Masateru; Nakano, Daisuke; Kinjo, Junei
Abstract The isolation of five novel natural sulfoxides as well as the elucidation of their relative structures are reported.